Suspected coronary artery disease and myocardial infarction with normal coronary angiography: a heterogeneous but benign condition? - Moreira, Nádia (2013)
Introduction: Previous follow-up studies of patients with symptoms and/or non-invasive tests suggestive of ischemia or an acute coronary syndrome and a normal coronary angiogram have reported a good prognosis. Objectives: The aim of this study was to evaluate the clinical characteristics and outcome of a cohort of patients with suspected ischemic heart disease and normal coronary arteries. Methods: A clinical follow-up was performed of 607 patients (mean age 62 ± 11 years) with symptoms or non-invasive tests suggestive of ischemia (544) or myocardial infarction (63) and normal coronary angiography. The occurrence of major cardiac events or of readmission due to chest pain was recorded during a mean follow-up of 33.6 ± 9.5 months after angiography. Results: Patients with myocardial infarction were older (65.4 ± 11.1 vs. 61.9 ± 10.7, p=0.05), and the majority were women (68.3%). Hypertension was reported by 65.5% of patients, diabetes by 17.9%, dyslipidemia by 58.6%, smoking by 14% and family history of coronary artery disease in 11%. During follow-up no patient died from cardiovascular causes; three patients (0.5%) suffered myocardial infarction and 50 (8.3%) had recurrent chest pain leading to emergency admission. Patients with myocardial infarction had more events (20.6%) than those referred for angiography due to symptoms and/or positive non-invasive tests for ischemia (7.4%) (log-rank chi-square test: 13.6, p<0.0005). Conclusion: The incidence of risk factors was high. Our data suggest that patients with a normal angiogram had a good prognosis in spite of their baseline clinical presentation. A significant number of patients showed persistence of symptoms.